EXPOSURE ANALYSIS OF INHALED HEAVY METALS IN BATIK CRAFTSMEN (CASE STUDY: LENDAH DISTRICT, KULONPROGO) - Fakhriah Basuki, Meutia
Continuously, the batik industry has spread and developed in almost all parts of Java. Lendah District, in Kulonprogo Regency, Yogyakarta, has several villages that have contributed to the development of the Indonesian batik industry. Activities in the batik production process using heavy metals contain risks to the health of workers. This study aims to measure the concentration of heavy metals in the inhaled air and the concentration of heavy metals in the blood of respondents, identify risk factors, the effect of inhaled heavy metals on blood concentrations, and assess the risk of exposure received by respondents. Respondents in this study were 16 workers and 16 non-working groups from three batik producers who were selected to measure the concentration of inhaled heavy metals (Mn, Cu, Zn, Ni, Co, As, Pb, and Cr) in workers and concentrations of heavy metals in the blood (Cr, Co, and Zn) in non-workers. The study was conducted cross-sectional with the X-Ray Fluorescence (XRF) analysis method for air samples and Instrumental Neutron Activation Analysis (INAA) for blood samples). In the analysis of air samples, there are heavy metal concentrations that are below the quality standard reference value, with the highest intake concentration being Cu metal in the color, canting and cap process worker respondents. From the results of blood sample analysis, it was found that the concentrations of CrB, CoB and ZnB 31,25% of workers respondents had a CrB concentration above the reference value, and 12,5% in the non-workers group of respondents HI value for inhalable heavy metals in workers was found to be 4.72x10-2, while the LECR value was 2.39 x 10-5.